Unusual Presentation of Dengue Fever Leading to Unnecessary Appendectomy - Kumar, Lovekesh (Case Rep Infect Dis, 2015)
Dengue fever is the most important arbovirus illness with an estimated incidence of 50–100 million cases per year. The common symptoms of dengue include fever, rash, malaise, nausea, vomiting, and musculoskeletal pain. Dengue fever may present as acute abdomen leading to diagnostic dilemma. The acute surgical complications of dengue fever include acute pancreatitis, acute acalculous cholecystitis, nonspecific peritonitis, and acute appendicitis. We report a case of dengue fever that mimicked acute appendicitis leading to unnecessary appendectomy. A careful history examination for dengue-related signs, and serial hemogram over the first 3-4 days of disease may prevent unnecessary appendectomy.